1976
DOI: 10.1021/bi00646a003
|View full text |Cite
|
Sign up to set email alerts
|

Pre-proparathyroid hormone: Analysis of radioactive tryptic peptides and amino acid sequence

Abstract: The amino acid sequence of bovine pre-proparathyroid hormone has been partially determined by analysis of the polypeptide labeled selectively with radioactive amino acids. Analysis of tryptic peptides containing methionine or lysine indicated that parathyroid hormone, proparathyroid hormone, and pre-proparathyroid hormone had several common peptides. Two lysine-containing peptides present in proparathyroid hormone but not in parathyroid hormone were also present in pre-proparathyroid hormone. In addition, pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0
1

Year Published

1976
1976
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(42 citation statements)
references
References 16 publications
2
39
0
1
Order By: Relevance
“…Recently, several large products have been shown to be synthesized in the wheat germ system supplemented with mRNAs coding for various secretory proteins (2)(3)(4)(5)(6)(7)(27)(28)(29). Since the extra portion of these cell-free products consists of a common sequence containing many hydrophobic amino acids at the amino terminus, it has been proposed that the large precursor molecules function to facilitate the transport of secretory proteins through the membrane (27)(28)(29)(30). Similarly, the large cell-free product of ACTH may represent the initial precursor that is rapidly converted to the large or …”
Section: Methodsmentioning
confidence: 99%
“…Recently, several large products have been shown to be synthesized in the wheat germ system supplemented with mRNAs coding for various secretory proteins (2)(3)(4)(5)(6)(7)(27)(28)(29). Since the extra portion of these cell-free products consists of a common sequence containing many hydrophobic amino acids at the amino terminus, it has been proposed that the large precursor molecules function to facilitate the transport of secretory proteins through the membrane (27)(28)(29)(30). Similarly, the large cell-free product of ACTH may represent the initial precursor that is rapidly converted to the large or …”
Section: Methodsmentioning
confidence: 99%
“…Messenger RNAs that encode for secretory proteins direct the synthesis in various cell-free systems of precursor forms (designated pre) containing an extra N-terminal sequence of about 25 amino acids [1][2][3][4][5][6][7][8]. It has been suggested that the extra protein portion plays a role in mediating the formation of membranebound ribosomal complexes [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The nucleotide sequence coding for antifreeze peptide was preceded by 63 bases coding for a leader sequence of21 amino acids. Similar to leader peptides for many of the secretory proteins (33,34), the leader sequence for antifreeze begins-with methionine and contains large numbers of hydrophobic amino acids.…”
mentioning
confidence: 99%